Civil Liability of A Doctor In Malpractice Cases - Rizka Ananda Putri Aji; Rocky Marbun (Eduvest - Journal of Universal Studies, 2022)
The right to health is part of human rights guaranteed in the constitution. The state is obliged to strive for the fulfillment of these rights through the provision of health services. Concerning health services, the existence of doctors plays an important role. Juridically the medical profession has been regulated in “Law Number 29 of 2004 concerning the Medical Profession”. Based on the law, the relationship between doctor and patient is based on trust. In carrying out their duties, of course, doctors must hold fast to prioritizing the health of patients. However, there are malpractice actions that occur, causing harm to the patient. Juridically this is certainly a problem regarding the responsibility of doctors to patients. Therefore, in this paper, the author discusses how doctors are responsible for malpractice actions from the perspective of civil law. The method used in this paper is normative juridical with a statutory and conceptual approach.